Peranan Freight Forwarder dalam Pengurusan Pemberitahuan Ekspor Barang pada Kantor BEA dan Cukai Belawan dengan Sistem Portal Pengguna Jasa oleh PT. Kemasindo Cepat Medan: Penelitian - Meriah Kita Deliani; Fahira Aulia (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the role of freight forwarders in managing Export Declaration through the service user portal system at the Belawan Customs and Excise Office, with a case study at PT. Kemasindo Cepat Medan. Freight forwarders play a vital role as service providers responsible for handling export documentation and transportation on behalf of shippers or consignees. The preparation of Export Declaration process is conducted based on supporting documents submitted by exporters, including invoices, packing lists, shipping instructions, certificates of origin, phytosanitary certificates, and bills of lading. The Export Declaration process is carried out by EMKL (Sea Freight Forwarding) services within freight forwarding companies. This study also identifies several obstacles encountered during the Export Declaration process submission process, such as network disruptions in the Indonesia National Single Window (INSW) system, which may delay submission, and data input errors related to export licensing that result in rejection notices from Customs. Once corrected and resubmitted, the approved Export Declaration process receives an Export Service Note. The research methodology employs field research through direct observation and interviews, as well as library research by reviewing relevant literature and references.